Attitudes and practices towards abate application in a village in Akinyele local government area of Oyo State, Nigeria (2001)
A study was carried out in Oyeteju Village in Akinyele Local Government Area of Oyo State to determine attitudes of the villagers to treating their drinking pond with Abate (Temephos). The findings showed that all women respondents fetched all their drinking water from the village pond. They all claimed to filter the drinking water, 83.3% claimed to add alum while 25% claimed to boil water. Only 75% knew why Abate was applied to pond despite previous education on Abate. 41.7% support Abate application because it will kill the guineaworm 'germs’ in water while 25% Support it because it will bring about good health to villagers. All the respondents claimed not to be affected by the application of Abate to pond water despite the fact that 33.3% said the pond water turned black while 8.3% said it turned reddish. Their strong belief in their pond which is their god and the colour change did not make the villagers go against the application of Abate to their pond. This was so because health education on Abate preceded its application. It was unfortunate however that the Abate application was not sustained in the village. Abate application in this village was accepted as a temporary measure while villagers wait expectantly for their own safe source of water preferably a borehole. The study shows the need for health education to proceed the application of Abate and the need to train villagers on how to apply the Chemical in order to sustain the application for effective control.